Morphology evolution and performance of zinc electrode in acid battery environment with ionic liquid. (March 2022) - Xie, Zhipeng; Xin, Meiqing; Wei, Lulu; Rao, Xianfa; Zeng, Min; Liu, Baixiong; Zhang, Qian
Highlights: Ionic liquid forms a layer of liquid film at the electrode/electrolyte. The structure of liquid film is different from that of the body solution, and the liquid film can control the morphology evolution and performance of zinc electrode. The dissolution morphology of zinc electrode is similar to its deposition morphology, which means that the morphology evolution is reversible. The reversible evolution of zinc electrode morphology is accompanied by significant improvement of the performance of zinc electrode. Abstract: In order to explore the correlation between the morphology evolution of zinc electrode and its performance in acid battery environment, we used ionic liquid to regulate the morphology evolution of zinc electrode and measured its performance during the deformation process. Ionic liquids, 1-ethyl-3-methylimidazolium acetate (EMIA), 1-ethyl-3-methylimidazolium trifluoroacetate (EMITfa) and 1‑butyl‑3-methylimidazolium trifluoromethanesulfonate (BMITfms) were added to Zn(CH3 SO3 )2 electrolyte separately, and evaluated in a zinc symmetric battery (ZSB). The dissolution morphology of zinc electrode is completely different from its deposition morphology, with the increase of battery voltage, when 1% EMIA is added to the electrolyte. When 1% EMITfa is present in the electrolyte, the dissolution morphology of zinc electrode is partially similar to its deposition morphology, and the decrease of battery voltage is 0.1622 V. When the electrolyte contains 1% BMITfms, the dissolution morphology of zinc electrode is very similar to its deposition morphology, and the decrease of battery voltage is 0.4948 V. The similarity between dissolution morphology and deposition morphology of zinc electrode is due to the reversible change of zinc electrode morphology which is beneficial to the improvement of electrode performance.